Note su religione e Gestalt politica nel primo Hegel (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. “La grande tragedia del popolo ebraico” - 2. Il superamento della scissione tra religione, filosofia e politica - 3. La “terza forma di religione” e la ricostruzione dell’ethos pubblico.Notes on religion and political Gestalt in the young HegelABSTRACT: The young Hegel identifies in the Jewish theocracy a model based on the split between divine and human, finite and infinite which confines man in an irrecoverable subordination and separation from nature and the rest of mankind. Hegel contrasts it with the idea of the Greek polis and its religion as a strengthening of ethical and political unity. Christ hasn’t succeeded in bridging the rift which marks not only the Jewish culture but also reproduces itself in modern intellectualism, which proceeds by separations and oppositions and culminates in the abstractness of modern law. Christ founded a community of love, renouncing the confrontation with reality, supinely accepted; nevertheless, the Christian idea of incarnation, together with the Greek suggestion of the unity of the being as a whole, seems to be decisive for the Hegelian attempt to think of the philosophical unity of opposites, indicating a way that is also religious (as visible union of the community in the cult) and political (as sacrificing of that which is particular and egoistic). In the transition from the Frankfurt to Jena, Christianity is recovered by Hegel as a premise for a new religion that ought to overcome the oppositions of modern intellectualism and rediscover the unity of the popular ethos.